Link and Match : Sinkronisasi Pembelajaran Akuntansi Vokasi dengan Karir Akuntan Era Society 5.0 - Dewiyanti, Sarah; Julaytenth, Muhammad Abdi Munsyii; Rohana, Sinar; Siregar, Hilda Octavana (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2021)
Vocational accounting education is education that prepares students andstudents to become reliable accountants in the future. By prioritizing the focus ofpractice-based learning rather than theory, vocational accounting graduatesboth at the vocational and diploma level are believed to make a majorcontribution to the progress of the nation. However, in its implementation thereare still many cases of learning in the field of accounting that do not support theneeds of the world of work, especially in the era of society 5.0. This study aimsto analyze the synchronization of vocational accounting learning with the needsof the workforce in the era of society 5.0 and the concept of vocationalaccounting learning that is in accordance with the needs of the workforce in theera of society 5.0. This research is a type of descriptive qualitative research. Thesubjects of this research are students majoring in accounting, while the object ofthis research focuses on the Special Region of Yogyakarta. The results of thisstudy are that there is a lack of synchronization of accounting learning inseveral vocational schools and universities with the needs of the businessworld/industrial world which are increasingly leading to the era of society 5.0.The government is now increasingly concerned with vocational education withthe link and match program initiated by the Director General of VocationalEducation so that there is a need for a learning curriculum that is closely relatedto the needs of the business world/industrial world.